Possibilities for applying the circular economy in the aerospace industry: Practices, opportunities and challenges - Dias, Veruska Mazza Rodrigues; Jugend, Daniel [UNESP]; Fiorini, Paula de Camargo; Razzino, Carlos do Amaral [UNESP]; Pinheiro, Marco Antonio Paula [UNESP] (Elsevier, 2022)
Although recent studies have pointed out the circular economy (CE) as one of the main trends in environmental sustainability, little is known about its applications in the aerospace industry. Addressing this gap, the objective of this study was to explore the possibilities of CE application in the aerospace industry. This research makes two contributions to the field. Firstly, the CE-related practices applicable to the aerospace industry were identified and analyzed. Secondly, the main practices were evaluated in three companies that develop and manufacture aerospace products in the global scenario, resulting in a guidance framework of CE practices for the aerospace industry. Among the main findings, it was observed that: (i) financial benefits have stimulated companies towards the application of circular strategies; (ii) ethanol has been used as an alternative and renewable fuel; (iii) several materials are reused and recycled in this and in different industrial sectors; and (iv) the use of Industry 4.0 technologies, such as artificial intelligence, virtual reality, drones and additive manufacturing drive CE in the aerospace industry.
Keywords: Aerospace industry; Circular business models; Digital transformation; Sustainable design